Effects of the primary explosion site and bulk cloud in VCE prediction: A comparison with historical accidents. Issue 2 (11th September 2014) - Bauwens, Carl Regis; Dorofeev, Sergey B.
<x xml:space="preserve">Abstract</x> A model for predicting vapor cloud explosion blast loads is described extending a previously developed model. The model considers the contribution of a Primary Explosion Site (PES) as well as the bulk effect of the total flammable cloud. The model results are then compared with historical accidents and other commonly used models considering a single PES. Four historical events are examined: the Flixborough accident of 1974, the Texas City accident of 2005, the Phillips 66 accident of 1989, and the Buncefield incident of 2005. It is found that the combined model produced pressure and impulse values consistent with the damage observed. If the contribution of the total cloud is not considered, the far field pressure, which included overpressures up to 0.35 bar, was underpredicted and impulse was significantly underpredicted. The other methods, produced, in general, significantly lower overpressures and impulses when compared with the damage indicators seen in the explosion accidents. © 2014 American Institute of Chemical Engineers Process Saf Prog 34: 147–153, 2015